Gonadal function in patients with beta thalassaemia major. Issue 2 (February 1988) - De Sanctis, V; Vullo, C; Katz, M; Wonke, B; Tanas, R; Bagni, B
Abstract : Endocrine studies were made on 23 female patients aged 13 to 29 years, with delayed puberty or primary amenorrhoea and beta thalassaemia major, and 12 healthy controls, of whom six were prepubertal and six were in Tanner's stage 3-4. Each patient and control received a single intravenous dose of 100 micrograms gonadotrophin releasing hormone (GnRH), and one week later, 10 U/kg body weight of human menopausal gonadotrophin (hMG) to stimulate ovarian function. The patients had decreased gonadotrophin reserves when compared with those of normal controls, only one of 23 patients had an intact luteinising hormone and follicle stimulating hormone response. Most of the thalassaemic patients with delayed puberty showed normal gonad response to human menopausal gonadotrophin (hMG), but three had very low responses, when compared with that of controls. The gonadal failure was even more severe in four of six patients with primary amenorrhoea. It is important to assess hypothalamic-pituitary-gonadal function in young women with beta thalassaemia major, so that those with glandular dysfunction may be started on replacement therapy.